Pregnancies of women with epilepsy: a population-based study in Iceland - Olafsson, E; Hallgrimsson, J T; Hauser, W A; Ludvigsson, P; Gudmundsson, G (Epilepsia, 2009)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field PURPOSE: Women with epilepsy who become pregnant are commonly considered to be at high risk for complications during pregnancy or delivery. The offspring are also considered to have increased risk of perinatal mortality, congenital malformations, and maturational delay. Because few of these studies are population based, potential bias exists because of selection. METHODS: We performed a historical population-based cohort study in Iceland to determine the prevalence of epilepsy among pregnant women, to identify pregnancy and delivery complications in women with epilepsy, and to determine the outcome of their pregnancies as compared with that in the general population of Iceland. We identified all women with active epilepsy who gave birth during a 19-year period in Iceland. RESULTS: In this population, 3.3 in 1,000 pregnancies involve mothers with active epilepsy. The frequency of adverse events (AE) during pregnancy in the women with epilepsy is similar to that observed among all live births in the population, but cesarean section was performed twice as frequently as in the general population. Perinatal mortality rate and mean birth weight are not significantly different in the offspring of women with epilepsy as compared with rest of the population. The risk of major congenital malformations (MGM) is increased 2.7-fold over that expected when a mother is treated with antiepileptic drugs (AEDs) during a pregnancy. CONCLUSIONS: Our study indicates that the rate of complications of pregnancy in mothers with active epilepsy is low and similar to that of the general population with epilepsy. Use of AEDs by the mother during pregnancy significantly increases the risk of MGM in the offspring.